Young people, welfare and crime : governing non-participation - Fergusson, Ross (Policy Press, 2016)
Mass youth unemployment is now endemic and almost ubiquitous in the global north and south alike. This book offers an original and challenging interpretation of the ways in which young people's unemployment and general non-participation is becoming marginalised and criminalised. It re-examines the causes and consequences of non-participation from an unusually wide range of disciplines, using an innovative theorisation of the fast-changing relationships between extended studentship, welfare provision, labour market restructuring and crime. This approach offers an understanding of what it means for young people to be socially re-positioned and economically excluded in increasingly unequal societies, in and beyond the UK.